Primary gastric squamous cell carcinoma – a case report of diagnosis, treatment, histological findings and follow-up - Schonhart, Luisa; Kaiser, René; Schmidt, Roland; Sailer, Adrian; Steinestel, Konrad; Schneider-Kappus, Wolfgang; Beltzer, Christian (Zeitschrift für Gastroenterologie, 2022)
Primary squamous cell carcinoma (PSCC) of the stomach is a rare oncologic disease with a reported incidence of only 0.04%. Therefore, there are no evidence-based recommendations for treatment. We present the case of a 73-year-old patient with PSSC. Multivisceral resection had to be performed to achieve tumor-free resection margins. Preoperative investigations, surgical treatment, histologic criteria and findings, and follow-up are presented.
Keywords: Magenkarzinom; Plattenepithelkarzinom; Multiviszeralresektion; Endosonografie